Design and Simulation of a 1 DOF Planetary Speed Increaser for Counter-Rotating Wind Turbines with Counter-Rotating Electric Generators - Neagoe Mircea; Saulescu Radu; Jaliu Codruta (MDPI, Basel, Switzerland, 2019)
The improvement of wind turbine performance poses a constant challenge to researchers and designers in the field. As a result, the literature presents new concepts of wind turbines (WTs), such as: counter-rotating wind turbines (CRWTs) with two coaxial wind rotors revolving in opposite directions, WTs with higher-efficiency and downsized transmission systems, or WTs with counter-rotating electric generators (CREGs). Currently, there are a few solutions of WTs, both containing counter-rotating components; however, they can only be used in small-scale applications. Aiming to extend the use of WTs with counter-rotating wind rotors (CRWRs) and CREGs to medium- and large-scale applications, this paper introduces and analyzes a higher-performance WT solution, which integrates two counter-rotating wind rotors, a 1 degree of freedom (DOF) planetary speed increaser with four inputs and outputs, and a counter-rotating electric generator. The proposed system yields various technical benefits: it has a compact design, increases the output power (which makes it suitable for medium- and large-scale wind turbines) and allows a more efficient operation of the electric generator. The kinematic and static computing methodology, as well as the analytical models and diagrams developed for various case studies, might prove useful for researchers and designers in the field to establish the most advantageous solution of planetary speed increasers for the CRWTs with CREGs. Moreover, this paper extends the current database of WT speed increasers with an innovative concept of 1 DOF planetary gearbox, which is subject to a patent application.
Keywords: wind turbine; counter-rotating wind rotors; counter-rotating electric generator; speed increaser; kinematic and static modelling; operating point